Custo de deslocamento como fator decis??rio sobre demandas trabalhistas no Brasil - Marques, Marcelo Barros (2017)
The study analyzes the hypothesis that the distance between the residence of the individual jurisdiction and the seat of the Labor Court of first instance, affects decision on whether or not to file a labor claim. The study was structured in two stages. The first deals with the theoretical discussion of the relation distance versus labor demand, based on consumer theory. The second stage deals with empirical research on the effects of socioeconomic, geographic and labor market factors on the labor demands from 2001 to 2014 in the 24 regions of Labor Justice in Brazil. The information collected is dealt with in panel data, in order to evaluate the effects of the explanatory variables referring to the above mentioned factors on the labor demands, with special interest on the parameter related to the distance of the jurisdiction. As a result, it is observed that the behavior of explanatory variables, commonly used in similar models, such as income, education and GDP, show the expected trend over the dependent variable. It is verified that, in fact, the attribute relative to the distance of the jurisdiction of its seat reflects in the degree of labor suit judgments, objective of this work. Therefore, it is not rejected the hypothesis of the existence of a relationship between the distance of residence of the individual and the seat of the Labor Court of first instance with a factor relevant to the decision making in filing or not a labor claim.